Computer and Information Sciences 31st International Symposium, ISCIS 2016, Kraków, Poland, October 27-28, 2016, Proceedings - Czachórski, Tadeusz; Gelenbe, Erol; Grochla, Krzysztof; Lent, Ricardo (Communications in Computer and Information Science, 2016)
Information Systems and Communication Service; Artificial Intelligence (incl. Robotics); Computer Communication Networks; Software Engineering/Programming and Operating Systems; Probability and Statistics in Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics